Inter-sectoral cooperation for Afghan refugee education in Iran - Shammout, R; Vandecasteele, O (Refugee Studies Centre, University of Oxford, 2019)
A recent decree in Iran removed a legal barrier to undocumented refugee children attending school but other barriers remain. One non-governmental organisation discusses the successes and challenges of adopting an inter-sectoral approach to breaking down these barriers.